Sejarah Peradilan Agama di Indonesia - Akram, Andi (Fakultas Syariah IAIN Purwokerto, 2008)
The up and down of Islamic court in Indonesia is related to the dynamic of social and politic. In colonialism era, this court is concerned only in marriage, divorce, and marriage reconciliation . Nowadays, according to UU no. 4 th. 2004, its function is divided into three parts executive, legislative, and judicial.